2021
DOI: 10.21511/ppm.19(3).2021.28
|View full text |Cite
|
Sign up to set email alerts
|

Determining the importance of high-reliability healthcare organizations during the Covid-19 pandemic: Evidence from healthcare workers in Turkey

Abstract: The Covid-19 pandemic has caused changes in the social and economic environments for healthcare. Particularly, to avoid spreading the Coronavirus pandemic, release the stress among healthcare workers, and make them work effectively during the epidemic, high-reliability healthcare organizations give great importance to the improvement of their functions. This study aims to show the importance of high-reliability healthcare organizations comparing their effectiveness during a pandemic by applied qualitative rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, high reliability is a mix of organizational support and resources supplied to strengthen employees' strong conviction in and acceptance of organizational objectives, as well as a genuine desire to stay with the organization and contribute effectively to its goals (Mazdeh & Hesamamiri, 2014;Mura et al, 2017;Meyer, 2018;Labrague & De los Santos, 2020;). All of these aspects play a role in boosting the organization's success and ensuring that essential organizational features -including interaction, communication, motivation, goal setting, control, and performance -are met (Hammer, 1979 ;Meyer & Meyer, 2020;Bilan et al, 2020;Sarihasan, et al, 2021). As a result, businesses look for ways to improve their capacity to react to and handle unforeseen conditions during a crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, high reliability is a mix of organizational support and resources supplied to strengthen employees' strong conviction in and acceptance of organizational objectives, as well as a genuine desire to stay with the organization and contribute effectively to its goals (Mazdeh & Hesamamiri, 2014;Mura et al, 2017;Meyer, 2018;Labrague & De los Santos, 2020;). All of these aspects play a role in boosting the organization's success and ensuring that essential organizational features -including interaction, communication, motivation, goal setting, control, and performance -are met (Hammer, 1979 ;Meyer & Meyer, 2020;Bilan et al, 2020;Sarihasan, et al, 2021). As a result, businesses look for ways to improve their capacity to react to and handle unforeseen conditions during a crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the healthcare setting, management must consider the coping strategies for HWs work resumption to recover the workers' enthusiasm to face future uncertainties through addressing the threats that workers bring to their workplaces, such as social hypochondria, suspicion, and massive distrust; promoting diversity and innovation; recovering trust and inspiration [106]. As mindfulness, some coping strategies should help reduce RTW-related stress and anxiety, increasing resilience and improving flexibility [107]. Zheng N et al analysed these factors, showing that managers should adopt effective intervention measures to address returning personnel's physical and mental health by considering several individual parameters, such as roles and cultural adaptation, self-efficacy, optimism, and resilience [84].…”
Section: Psychosocial Aspectsmentioning
confidence: 99%
“…The study found a relationship between the severity and timing of disease suppression through disease progression and social distancing in the population. Sarihasan, Oláh [ 27 ] discovered that in high-reliability healthcare companies, shared knowledge patterns, self-care, and awareness of corona infection repercussions at work have a larger role in preventing Covid-19. Khan et al [ 42 ] explored the impact of policy pleasured taken by the South Asian region to curb the COVID-19 infection employing panel data.…”
Section: Introductionmentioning
confidence: 99%